Metal-enriched Neutral Gas Reservoir around a Strongly Lensed Low-mass Galaxy at z = 4 Identified by JWST/NIRISS and VLT/MUSE - Xiaojing Lin; Zheng Cai; Siwei Zou; Zihao Li; Zuyi Chen; Fuyan Bian; Fengwu Sun; Yiping Shu; Yunjing Wu; Mingyu Li; Jianan Li; Xiaohui Fan; et al. (The Astrophysical Journal Letters, 2023)
Direct observations of low-mass, low-metallicity galaxies at z ≳ 4 provide an indispensable opportunity for detailed inspection of the ionization radiation, gas flow, and metal enrichment in sources similar to those that reionized the universe. Combining the James Webb Space Telescope (JWST), Very Large Telescope/MUSE, and Atacama Large Millimeter/submillimeter Array, we present detailed observations of a strongly lensed, low-mass (≈10 ^7.6 M _⊙ ) galaxy at z = 3.98 (also see Vanzella et al.). We identify strong narrow nebular emission, including C iv λ λ 1548, 1550, He ii λ 1640, O iii ] λ λ 1661, 1666, [Ne iii ] λ 3868, [O ii ] λ 3727, and the Balmer series of hydrogen from this galaxy, indicating a metal-poor H ii region (≲0.12 Z _⊙ ) powered by massive stars. Further, we detect a metal-enriched damped Ly α system (DLA) associated with the galaxy with the H i column density of N _H I ≈ 10 ^21.8 cm ^−2 . The metallicity of the associated DLA may reach the supersolar metallicity (≳ Z _⊙ ). Moreover, thanks to JWST and gravitational lensing, we present the resolved UV slope ( β ) map at the spatial resolution of ≈100 pc at z = 4, with steep UV slopes reaching β ≈ −2.5 around three star-forming clumps. Combining with low-redshift analogs, our observations suggest that low-mass, low-metallicity galaxies, which dominate reionization, could be surrounded by a high covering fraction of the metal-enriched, neutral-gaseous clouds. This implies that the metal enrichment of low-mass galaxies is highly efficient, and further supports that in low-mass galaxies, only a small fraction of ionizing radiation can escape through the interstellar or circumgalactic channels with low-column-density neutral gas.